Anti-proliferative effects of pandan leaves (Pandanus amarylfolius), kantan flower(Etlingera elatior) and turmeric leaves (Curcuma longa). - Chong, Hueh Zan; Rahmat, Asmah; Md. Akim, Abdah; Mohamed Alitheen, Noorjahan Banu; Othman, Fauziah; Cheng, Gwendoline Lian Ee (Emerald Group Publishing, 2011)
Purpose – The purpose of this paper is to screen cytotoxic activities of commonly used culinary plants in Malaysia, Pandanus amaryllifolius (daun pandan), Curcuma longa (turmeric leaves) and Etlingera elatior (kantan flower) against selected cancer cell lines.